(untitled) (Universal International Scientific Journal, 2026)
The article discusses teaching children to observe animate and inanimate objects of nature, forming skills of environmentally friendly behavior in nature while observing the rules of safe work in nature, and fostering a sense of empathy and a desire to help objects of nature in need: plants, insects, animals, birds, and people.